2013
DOI: 10.1371/journal.pone.0079662
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteases and Tissue Inhibitors of Metalloproteinases in Medial Plica and Pannus-like Tissue Contribute to Knee Osteoarthritis Progression

Abstract: Osteoarthritis (OA) is characterized by degradation of the cartilage matrix, leading to pathologic changes in the joints. However, the pathogenic effects of synovial tissue inflammation on OA knees are not clear. To investigate whether the inflammation caused by the medial plica is involved in the pathogenesis of osteoarthritis, we examined the expression of matrix metalloproteinases (MMPs), tissue inhibitors of metalloproteinases (TIMPs), interleukin (IL)-1β, and tumor necrosis factor (TNF)-α in the medial pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 45 publications
9
45
0
Order By: Relevance
“…Our previous in vitro studies of human fibroblast-like synoviocytes suggest that elevated periostin levels mediate increases in the concentration of MMP-9 (15). Several studies have reported increases in the MMP-9 expression levels in knee synovial fluid during the progression of OA (32,33). The present study showed that the capacity of OA-associated synovial cells to produce MMP-2 and MMP-3 was enhanced by periostin stimulation (Figure 3A and B).…”
Section: Discussionsupporting
confidence: 64%
“…Our previous in vitro studies of human fibroblast-like synoviocytes suggest that elevated periostin levels mediate increases in the concentration of MMP-9 (15). Several studies have reported increases in the MMP-9 expression levels in knee synovial fluid during the progression of OA (32,33). The present study showed that the capacity of OA-associated synovial cells to produce MMP-2 and MMP-3 was enhanced by periostin stimulation (Figure 3A and B).…”
Section: Discussionsupporting
confidence: 64%
“…Our further studies not only disclosed the kinematic relationship between the medial plica with the medial femoral condyle during knee motion in vivo [5], but also implied the close interplay between this structure and the medial femoral condyle [6]. More recently we have found [7,8] that the repeated injuries elicited by this abrasion phenomenon might trigger interleukin-1β (IL-1β) production in medial plica, thus enhancing the expression of matrix metalloproteinase-3 (MMP-3). Based on these findings, a concept of arthroscopic medial release (AMR) for the treatment of OA of the medial compartment of the knee joint was developed [9].…”
Section: Introductionmentioning
confidence: 67%
“…This global management concept was based on our understanding of the medial abrasion phenomenon as a cause of knee OA [4][5][6][7][8]. At follow-up after more than one year, patient satisfaction rate was 100% for patients who received arthroplasty, including 71 (8.4%) UKA and 116 (13.8%) TKA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations